Political Communication Strategy through Unique Posters: A Critical Discourse Analysis Study - Ririn Sulistyowati (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
Political communication is an important part of a country. Through this kind of communication, a piece of information will be properly conveyed. Using unique sentences in posters’ demonstrations is a political communication strategy to attract the government’s attention. This study discussed the unique posters used by students when conducting demonstrations as a form of political communication. This study explained the discourse patterns used by students in demonstration posters through critical discourse analysis using Norman Fairclough’s theory. In addition, this study also revealed how the posters’ language was used as a form of social practice in political communication from the public to the government. Based on the analysis that the researcher had done, it can be concluded that the political communication strategy conducted by students through unique posters in demonstrations has three dimensions: text, discourse practice, and sociocultural practice.